2022
DOI: 10.3389/fmicb.2022.1010513
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of transferable oxazolidinone resistance genes in enterococcal isolates from a swine farm in China

Abstract: The appearance of transferable oxazolidinone resistance genes poses a major challenge to public health and environmental safety. These genes not only lead pathogenic bacteria to become resistant to linezolid but also reduce sensitivity to florfenicol, which is widely used in the veterinary field. To verify the dissemination of oxazolidinone resistance genes in enterococcal isolates from pigs at different production stages in a swine farm in China, we collected 355 enterococcal isolates that were resistant to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The presence of plasmids carrying ARGs indicated that Enterococcus isolates could transfer between them and promote the further spread of linezolid resistance genes (Cinthi et al, 2022b). Meanwhile, the presence of other ARGs on the plasmids, such as fexA and erm(A), may contribute to the persistence of linezolid resistance genes (Tang et al, 2020(Tang et al, , 2021Huang et al, 2022). With extensive studies on linezolid resistance genes, various variants have gradually emerged, such as cfr(D), cfr(B), poxtA2, and optrA, suggesting that further monitoring of enterococcal resistance is needed (Saavedra et al, 2020;Cinthi et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of plasmids carrying ARGs indicated that Enterococcus isolates could transfer between them and promote the further spread of linezolid resistance genes (Cinthi et al, 2022b). Meanwhile, the presence of other ARGs on the plasmids, such as fexA and erm(A), may contribute to the persistence of linezolid resistance genes (Tang et al, 2020(Tang et al, , 2021Huang et al, 2022). With extensive studies on linezolid resistance genes, various variants have gradually emerged, such as cfr(D), cfr(B), poxtA2, and optrA, suggesting that further monitoring of enterococcal resistance is needed (Saavedra et al, 2020;Cinthi et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%